2018
DOI: 10.1111/1759-7714.12584
|View full text |Cite
|
Sign up to set email alerts
|

Manganese‐12 acetate suppresses the migration, invasion, and epithelial–mesenchymal transition by inhibiting Wnt/β‐catenin and PI3K/AKT signaling pathways in breast cancer cells

Abstract: BackgroundBreast cancer is the leading cause of cancer‐related death in the world, and it is of great value to reveal the molecular mechanisms of breast cancer progression and develop new therapeutic targets.MethodsTranswell assay is used to analyze the migration and invasion of breast cancer cells. Real‐time PCR and western blotting assay are applied to detect the expression levels of epithelial–mesenchymal transition markers and the key members of Wnt/β‐catenin and PI3K/AKT signaling pathways.ResultsManganes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Numerous studies have reported that EMT is mediated by multiple pathways, including the Smad, MAP kinase (MAPK), and phosphatidylinositol 3-kinase (PI3K) pathways (13,22,41). Experimental Smad3-deficient mouse models of EMT and fibrosis demonstrated that Smad3 signaling is important in fibrosis (23).…”
Section: L1020mentioning
confidence: 99%
“…Numerous studies have reported that EMT is mediated by multiple pathways, including the Smad, MAP kinase (MAPK), and phosphatidylinositol 3-kinase (PI3K) pathways (13,22,41). Experimental Smad3-deficient mouse models of EMT and fibrosis demonstrated that Smad3 signaling is important in fibrosis (23).…”
Section: L1020mentioning
confidence: 99%
“…The migratory and invasive ability of prostate cancer cells was measured in a Transwell chamber [ 23 ]. Before the start of the invasion test, Matrigel should be applied to the membrane 6 hours in advance.…”
Section: Methodsmentioning
confidence: 99%
“…Transwell chamber [23]. Before the start of the invasion test, Matrigel should be applied to the membrane 6 hours in advance.…”
Section: Transwell Cell Migration and Invasion Assaymentioning
confidence: 99%
“… 4 However, this approach can induce or aggravate lung damage, a condition referred to as mechanical ventilation-induced lung injury (VILI). 5 , 6 Adjuvant pharmacological approaches to reduce ARDS-associated pulmonary fibrosis have been highlighted as a potential means to improve morbidity and mortality rates. Over the past two decades, considerable research has focused on developing pharmacological therapies for ARDS, but results to date have been unsuccessful.…”
Section: Introductionmentioning
confidence: 99%